Sikap Implisit dan Eksplisit terhadap Iklan Kondom Sensual dan Simbolik pada Remaja - Ibadurrahman; Nurlyta Hafiyah (Fakultas Psikologi Universitas Pancasila, 2012)
The study was conducted to examine the implicit attitude and explicit attitude among adolescents toward sensual condom ads and symbolic condom ads. Implicit attitude was measured using the Implicit Association Test (IAT) and explicit attitude measured using a semantic differential scale. Participants are 40 adolescents, senior high school students, 16-18 years old in Jakarta. The results of this study indicated that adolescents have a positive implicit attitude toward sensual condom ads, but have a positive explicit attitude toward symbolic condom ads. The result indicated that sensual condom ads can be used as a message content targeted to adolescent.